Lack of Mycobacterium tuberculosis–specific interleukin‐17A–producing CD4+ T cells in active disease. Issue 4 (6th March 2013) - Perreau, Matthieu; Rozot, Virginie; Welles, Hugh C.; Belluti‐Enders, Felicitas; Vigano, Selena; Maillard, Michel; Dorta, Gian; Mazza‐Stalder, Jesica; Bart, Pierre‐Alexandre; Roger, Thierry; Calandra, Thierry; Nicod, Laurent; et al.
<x xml:space="preserve">Abstract</x> Protective immunity to Mycobacterium tuberculosis (Mtb) is commonly ascribed to a Th1 profile; however, the involvement of Th17 cells remains to be clarified. Here, we characterized Mtb‐specific CD4+ T cells in blood and bronchoalveolar lavages (BALs) from untreated subjects with either active tuberculosis disease (TB) or latent Mtb infection (LTBI), considered as prototypic models of uncontrolled or controlled infection, respectively. The production of IL‐17A, IFN‐γ, TNF‐α, and IL‐2 by Mtb‐specific CD4+ T cells was assessed both directly ex vivo and following in vitro antigen‐specific T‐cell expansion. Unlike for extracellular bacteria, Mtb‐specific CD4+ T‐cell responses lacked immediate ex vivo IL‐17A effector function in both LTBI and TB individuals. Furthermore, Mtb‐specific Th17 cells were absent in BALs, while extracellular bacteria‐specific Th17 cells were identified in gut biopsies of healthy individuals. Interestingly, only Mtb‐specific CD4+ T cells from 50% of LTBI but not from TB subjects acquired the ability to produce IL‐17A following Mtb‐specific T‐cell expansion. Finally, IL‐17A acquisition by Mtb‐specific CD4+ T cells correlated with the coexpression of CXCR3 and CCR6, currently associated to Th1 or Th17 profiles, respectively. Our data demonstrate that Mtb‐specific Th17 cells are selectively undetectable in peripheral blood and BALs from TB patients.